Titik Kontrol Kritis Pada Pengolahan Susu Pasteurisasi Di Koperasi Unit Desa (KUD) Dau Kabupaten Malang - Kristanti, Novita Dewi; Warnaen, Andi; Daning, Dewi Ratih Ayu (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2017)
Research on Critical Control Point in Pasteurized Milk Processing in KUD Dau aims to analyze the critical control points on the processing of pasteurized milk using a decision tree in KUD Dau. The method used is descriptive method quantitative survey research approach. Population and sample are officers at the post shelter, the driver's vehicle fleet tanker, tank officers in transit, the officer in pasteurized milk processing and sanitation workers in KUD Dau, the number of samples is 22 people targeted research. The analysis technique used is descriptive statistical techniques. Results of research Critical Control Point Pasteurized Milk Processing showed pasteurized milk produced by KUD Dau potentially contain Hazards B. containing food additives and nutritional value of milk. Danger D. pasteurized milk products likely to be contaminated again after processing and prior to packing. E Danger In pasteurized milk there is a potential danger in handling during distribution or handling by consumers. Danger F. There is no end of the heating process after packing or when cooked at home. The results of this study concluded that CCPs are pasteurized milk processing stages: milk reception in the post shelter, pasteurization and homogenization phase I, phase II pasteurization, flavor blending, storage and distribution.